2001
DOI: 10.1088/0953-4075/34/5/303
|View full text |Cite
|
Sign up to set email alerts
|

On the second Born approximation for laser-assisted electron-atom collisions

Abstract: The differential cross section for electron-hydrogen atom collisions in the presence of a CO2 laser field is analysed as a function of the incident electron energy. We show that the criticism of the second Born treatment of elastic scattering and excitation by fast electrons is unjustified for various geometrical configurations. Detailed calculations of the scattering amplitudes are performed by using the Sturmian basis expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…enhancement or diminution of the peak just seems to be reversed! It would be interesting to compare our experimental data with the results of more refined non-perturbative calculations taking target polarization or dressing of the initial state into account [24][25][26][27][28].…”
Section: Finally We Present Triply Differential Cross Sections Tdcsmentioning
confidence: 99%
“…enhancement or diminution of the peak just seems to be reversed! It would be interesting to compare our experimental data with the results of more refined non-perturbative calculations taking target polarization or dressing of the initial state into account [24][25][26][27][28].…”
Section: Finally We Present Triply Differential Cross Sections Tdcsmentioning
confidence: 99%
“…The semi-perturbative treatment of laser-assisted (e, 2e) reactions, described above for the case of an atomic hydrogen target, has been extended by Joachain et al [29], Khalil et al [31], Makhoute et al [32,44,46], Bouzidi et al [81] and Ajana et al [43,45] to laser-assisted (e, 2e) reactions in helium, for which the possibilities of performing experiments are more favorable. These studies also showed that the choice of the laser parameters can strongly influence the dynamics of such processes, and that target-dressing effects can be important.…”
Section: The Semi-perturbative Methodsmentioning
confidence: 99%
“…We present here a short description of our theoretical approach to deal with the electron's impact excitation of the helium atom in the presence of a laser field. A detailed description can be found in our previous works [32][33][34]. The scenario we considered here can be simplified into the following form:…”
Section: Theoretical Descriptionmentioning
confidence: 99%